2015
DOI: 10.3389/fgene.2015.00293
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the porcine species in biomedical research

Abstract: Since domestication, pigs have been used extensively in agriculture and kept as companion animals. More recently they have been used in biomedical research, given they share many physiological and anatomical similarities with humans. Recent technological advances in assisted reproduction, somatic cell cloning, stem cell culture, genome editing, and transgenesis now enable the creation of unique porcine models of human diseases. Here, we highlight the potential applications and advantages of using pigs, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
126
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(134 citation statements)
references
References 113 publications
1
126
0
7
Order By: Relevance
“…Several inbred lines were selected as homozygous for SLA in NIH miniature pigs for biomedical studies 38 . Previous and current studies showed the establishment of homozygosity in class II (observed heterozygosity, DRB1-0%; DQA1-0%; DQB1-34.72%) but not in class I genes (observed heterozygosity, SLA-1, 83% and SLA-2, 46.6%) 18,[20][21][22] for the breed.…”
Section: Discussionmentioning
confidence: 99%
“…Several inbred lines were selected as homozygous for SLA in NIH miniature pigs for biomedical studies 38 . Previous and current studies showed the establishment of homozygosity in class II (observed heterozygosity, DRB1-0%; DQA1-0%; DQB1-34.72%) but not in class I genes (observed heterozygosity, SLA-1, 83% and SLA-2, 46.6%) 18,[20][21][22] for the breed.…”
Section: Discussionmentioning
confidence: 99%
“…Porcine strains currently available for research include Yorkshire and Landrace farm pigs, and several minipig breeds such as Yucatan, Hanford, Sinclair, and Göettigen minipigs. 53 Young adult Yucatan minipigs weighing approximately 20-30 kg can grow to 50 kg at 9 months of age and will for Göettigen minipigs is roughly 40-50 kg. 53 Our lab has used domestic farm pigs (Yorkshire strain) for short-term studies, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…53 Young adult Yucatan minipigs weighing approximately 20-30 kg can grow to 50 kg at 9 months of age and will for Göettigen minipigs is roughly 40-50 kg. 53 Our lab has used domestic farm pigs (Yorkshire strain) for short-term studies, e.g. investigating the translatability of various tissue engineered nerve grafts from the rodent to porcine model and the mechanism of action of nerve regeneration following short-gap repair at acute time points.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have used multicore and graded index multimode fibres for the delivery of ultrashort pulse (USP) to demonstrate the laser ablation. Prior work has established pig tissue as an efficient medical model for several studies related to human diseases and is consequently applied in porcine vocal fold tissue resection using 1.5 ps laser pulses delivered through kagome lattice hollow core photonic crystal fibre for microsurgery . The microsurgery laser ablation on the vocal fold tissue has a depth and width of ablation of around 43 and 40 μm, respectively, at a pulse energy of 1.2 μJ.…”
Section: Introductionmentioning
confidence: 99%